2022
DOI: 10.3390/jmse10040454
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N-Oxide (TMAO) and Trimethylamine (TMA) Determinations of Two Hadal Amphipods

Abstract: Hadal trenches are a unique habitat with high hydrostatic pressure, low temperature and scarce food supplies. Amphipods are the dominant scavenging metazoan species in this ecosystem. Trimethylamine (TMA) and trimethylamine oxide (TMAO) have been shown to play important roles in regulating osmotic pressure in mammals, hadal dwellers and even microbes. However, the distributions of TMAO and TMA concentrations of hadal animals among different tissues have not been reported so far. Here, the TMAO and TMA contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…The TMAO content was much higher in the eggs of A. gigantea than crustaceans inhabiting shallow waters, while there was no significant difference in TMA contents ( Figure 5 ). These results are similar to those of previous studies that TMAO concentrations are significantly higher in hadal amphipods with similar levels of TMA among different tissues ( Liu et al, 2022 ). TMAO is produced by the oxidation of TMA under the action of the flavin monooxygenases (FMOs) ( Canyelles et al, 2018 ), while TMA is mainly formed by the consumption of carnitine choline by gut microorganisms ( Wang et al, 2011 ).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The TMAO content was much higher in the eggs of A. gigantea than crustaceans inhabiting shallow waters, while there was no significant difference in TMA contents ( Figure 5 ). These results are similar to those of previous studies that TMAO concentrations are significantly higher in hadal amphipods with similar levels of TMA among different tissues ( Liu et al, 2022 ). TMAO is produced by the oxidation of TMA under the action of the flavin monooxygenases (FMOs) ( Canyelles et al, 2018 ), while TMA is mainly formed by the consumption of carnitine choline by gut microorganisms ( Wang et al, 2011 ).…”
Section: Resultssupporting
confidence: 93%
“…Previous studies have reported that TMAO concentrations are significantly higher in the tissues of hadal species than shallow-water species ( Gillett et al, 1997 ; Samerotte et al, 2007 ; Liu et al, 2022 ). Likewise, the results of the present study revealed that TMAO contents were significantly higher in the eggs of hadal amphipods than those of shallow-water crustaceans, while TMA concentrations were similar ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations